2014
DOI: 10.1128/jcm.00469-14
|View full text |Cite
|
Sign up to set email alerts
|

Improved Detection of Bacterial Central Nervous System Infections by Use of a Broad-Range PCR Assay

Abstract: A universal PCR assay for bacteria and fungi detected meningitis pathogens in 65% of 20 cerebrospinal fluid (CSF) samples from patients with suspected central nervous system (CNS) infections compared to a 35% detection rate by culture and/or microscopy methods. Thus, the PCR assay can improve the diagnosis rate of infective meningitis when standard methods provide a negative result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…Many of the pathogens associated with CNS infections are detected by culture, microscopy, or antigen detection techniques. PCR is generally more reliable at detecting pathogens in the CSF, with substantially higher sensitivity than other diagnostic methods such as culture and enzyme-linked immunosorbent assay if the samples are collected at the appropriate time during the infection (16)(17)(18). PCR-based approaches for detecting multiple pathogens in a single array not only increase the number of pathogens that can be detected but also reduce the overall amount of time needed to rule out multiple pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the pathogens associated with CNS infections are detected by culture, microscopy, or antigen detection techniques. PCR is generally more reliable at detecting pathogens in the CSF, with substantially higher sensitivity than other diagnostic methods such as culture and enzyme-linked immunosorbent assay if the samples are collected at the appropriate time during the infection (16)(17)(18). PCR-based approaches for detecting multiple pathogens in a single array not only increase the number of pathogens that can be detected but also reduce the overall amount of time needed to rule out multiple pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed 75% sensitivity of conventional CSF culture compared with PCR-based diagnosis. 21 The low sensitivity could be due to the previous use of antimicrobials from the general practitioners that reduced the viable microbes in CSF. In this regard, ME FilmArray platform is a molecular method and empiric use of antimicrobials does not affect its result.…”
Section: Discussionmentioning
confidence: 99%
“…Timely access to enterovirus RT-PCR results have been shown to facilitate shorter hospital stays, reduce unnecessary antibiotic use, and lessens ancillary laboratory testing 5052 . Broad-range rRNA PCR techniques, which use single pair of primers targeting conserved regions of genes are successfully used for rapid detection and identification of bacterial pathogens and herpesviruses in the CSF 16, 53, 54 . Isothermal amplification-based techniques including loop-mediated isothermal amplification (LAMP) has been successfully developed to provide point care diagnosis within minutes to hours 55 .…”
Section: Molecular Methods In Diagnosis Of Cns Infectionsmentioning
confidence: 99%
“…When compared to conventional methods, molecular methods show greater detection rates: one study reported 16S rRNA PCR-based assays were able to accurately detect the causative organism in 65% of banked CSF samples, compared to 35% when using culture and microscopy 16 . In another report, improved diagnostic yield based on molecular methods were used to optimize antibiotic treatment of patients with infectious meningitis when conventional methods provided a negative result 17 .…”
Section: Introductionmentioning
confidence: 99%